Non-Articular Osseous Sarcoidosis: A Rare Case of Active Sarcoidosis with Progressive Lung Lesions and Normal Inflammation Biomarkers - Jing Zhang; Yu Hu; Peixin Dong; Hefang Guo; Lixia Huang; Lili Chen; Yanbin Zhou (Diagnostics)
Sarcoidosis is a rare multisystem inflammatory disease characterized by non-necrotizing granulomas, typically affecting the lungs, lymph nodes, skin, and bones. Due to its extreme clinical heterogeneity, diagnosis remains challenging. Within the skeletal system, the thoracic spine, ankles, and knees are the most commonly involved joints. We report a rare case of non-articular osseous sarcoidosis with progressive pulmonary lesions and persistently normal inflammatory biomarkers (ACE, CRP, ESR, IL-2, and TNF-α) that required differentiation from metastatic bone tumors and tuberculosis. Prior to presentation at our hospital, the patient did not respond to six months of anti-tuberculosis treatment and one month of systemic glucocorticoid therapy in three other hospitals. Based on lung and bone biopsies, she was finally diagnosed as having active sarcoidosis in our hospital. Despite 3 months of prednisone, pulmonary consolidation and bone lesions persisted until methotrexate was added. This case highlights the preference of combined glucocorticoid and methotrexate therapy for sarcoidosis with atypical osseous involvement and normal biomarkers, underscoring the urgent need for novel diagnostic tools to mitigate misdiagnosis.